2010
DOI: 10.1007/s10147-010-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative 18[F]-fluorodeoxyglucose positron emission tomography/computed tomography predicts early recurrence after pancreatic cancer resection

Abstract: Preoperative SUV(max) was higher in the recurrence group during the early postoperative period, and a high SUV(max) was a risk factor for early postoperative recurrence. Based on these results, we conclude that FDG-PET/CT is predictive of the recurrence of pancreatic cancer in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…In this study, we examined the prognostic value of MTV and TLG measured on preoperative 18 F-FDG PET/CT. The results of our study demonstrated that MTV and TLG are independent prognostic factors and had a stronger association with RFS and OS than SUVmax, which was used as the primary parameter in previous PET/CT studies (12)(13)(14)(15). MTV is defined as the volume of tumor tissue that shows increased 18 F-FDG uptake over a set threshold, which was an SUV of 2.5 in our study.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, we examined the prognostic value of MTV and TLG measured on preoperative 18 F-FDG PET/CT. The results of our study demonstrated that MTV and TLG are independent prognostic factors and had a stronger association with RFS and OS than SUVmax, which was used as the primary parameter in previous PET/CT studies (12)(13)(14)(15). MTV is defined as the volume of tumor tissue that shows increased 18 F-FDG uptake over a set threshold, which was an SUV of 2.5 in our study.…”
Section: Discussionmentioning
confidence: 54%
“…In patients with pancreatic cancer, several studies have demonstrated an important role for 18 F-FDG PET/CT in staging, detecting postoperative recurrence, and evaluating the response to treatment (6,(10)(11)(12)(13). Other studies have shown that the standardized uptake value (SUV) of primary pancreatic cancer lesions measured on 18 F-FDG PET/CT can help to predict recurrence in patients with pancreatic cancer (12,14,15). Recently, 18 F-FDG PET/CT-based volumetric imaging parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have also been suggested as prognostic factors for various neoplasms (16)(17)(18).…”
mentioning
confidence: 99%
“…In both studies, SUV was a significant, independent factor for OS by multivariate analysis (21,22). In 56 patients with PC before resection, a high SUV was a risk factor for early postoperative recurrence (23). In the present study on univariate analysis, SUV 1 and SUV 2 were predictors of survival in all patients and in the subgroup with localized PC.…”
Section: Discussionmentioning
confidence: 61%
“…The higher the baseline SUV max , the greater the likelihood of recurrence in the early postoperative period. SUV max may also be an independent predictor for overall survival in patients with locally advanced pancreatic cancer (32,33). In a study performed by Sperti et al, at 1-y follow-up, none of the patients with an SUV greater than 4.0 had survived, and 75% of those with an SUV less or equal to 4.0 were still alive (34).…”
Section: Pet/ct Applications Toward Prognosis Response To Therapy Rmentioning
confidence: 99%